Measurement of the B°-B° mixing parameter and the Z → bb forward-backward asymmetry - Dova, María Teresa (1994)
We have measured the time integrated B°-B° mixing parameter and the forward-backward asymmetry in the process e+e− → bb using hadronic events containing muons or electrons. The data sample corresponds to 1,044,000 hadronic decays of the Z. From a fit to the momentum and transverse momentum distributions for single lepton and dilepton events, we have determined the B°-B° mixing parameter to be χB = 0.123 =k 0.012 (stat.) -t- 0.008 (sys.), and the bb forward-backward asymmetry at the effective center-of-mass energy x/~ = 91.30GeV to be AbF , = 0.087 + 0.011 (stat.) =t= 0.004 (sys.) This measurement corresponds to a value of the effective electroweak mixing angle of sin20w = 0.2335 + 0.0021.